Manipulation of Defects for High‐Performance Thermoelectric PbTe‐Based Alloys. Issue 7 (14th April 2021) - Zhou, Jiayu; Wu, Yixuan; Chen, Zhiwei; Nan, Pengfei; Ge, Binghui; Li, Wen; Pei, Yanzhong
Abstract : 0D Point defects, 1D dislocations and 2D interfaces act as effective sources for scattering phonons due to the fluctuations in atomic mass and lattice strain. Dislocations have been demonstrated recently to enable a significant reduction in lattice thermal conductivity of PbTe, and a co‐substitution of Eu and Na at Pb site was found to effectively introduce dense in‐grain dislocations in p‐PbTe. This motivates this work to focus on a further PbSe alloying in Na0.03 Eu0.03 Pb0.94 Te for introducing point defects in addition to these dislocations, with participation of a further reduction in lattice thermal conductivity. The resultant extremely low lattice thermal conductivity (a minimum of ≈0.4 W m −1 K −1 ) in the entire temperature range leads to an eventual ≈30% enhancement in the average thermoelectric figure of merit zT in the working temperature range and a peak zT as high as ≈2.3 at 850 K in Na0.03 Eu0.03 Pb0.94 Te0.9 Se0.1 . Abstract : PbSe alloying in Na0.03 Eu0.03 Pb0.94 Te introduces point defects in addition to the dislocations, leading to a further reduction in lattice thermal conductivity. The resultant extremely low lattice thermal conductivity with a minimum of ≈0.4 W m −1 K −1 enables a ≈30% enhancement in the average zT and a peak zT as high as ≈2.3 at 850 K in Na0.03 Eu0.03 Pb0.94 Te0.9 Se0.1 .